Big Data in E-Learning: Review Study on Google Classroom Usage and Big Data Challenges - Widiasanti, Irika; Puteri, Anida Aulia Albarashwa; Savitri, Desi; Anjani, Diva; Nathania, Nasywa (Scripta : English Department Journal, 2023)
The use of Big Data in e-learning, especially on the Google Classroom platform, has become an increasingly important topic in education today. The challenges and benefits associated with using Big Data in e-learning have been the focus of research. This study aims to look at the use of Big Data in e-learning with a focus on Google Classroom and the challenges associated with its use. The method used is a literature review from previous studies related to this topic. The results show that the use of Big Data in e-learning can provide great benefits for educational institutions, such as increasing student engagement and making it easier for teachers to provide feedback. However, the use of Big Data in e-learning also has challenges that must be overcome, such as privacy issues, difficult data management, and data security. To overcome these challenges, strict and transparent privacy rules must be implemented, data analysis technologies such as big data analytics can be used for data management and analysis, and cybersecurity technologies such as data encryption can be used to protect data collected by e-learning platforms.